A theranostic PSMA ligand for PET imaging and retargeting of T cells expressing the universal chimeric antigen receptor UniCAR. (2nd November 2019) - Arndt, Claudia; Feldmann, Anja; Koristka, Stefanie; Schäfer, Martin; Bergmann, Ralf; Mitwasi, Nicola; Berndt, Nicole; Bachmann, Dominik; Kegler, Alexandra; Schmitz, Marc; Puentes-Cala, Edinson; Soto, Javier Andrés; et al.
ABSTRACT: Chimeric antigen receptor (CAR) T cells have shown impressive therapeutic potential. Due to the lack of direct control mechanisms, therapy-related adverse reactions including cytokine release- and tumor lysis syndrome can even become life-threatening. In case of target antigen expression on non-malignant cells, CAR T cells can also attack healthy tissues. To overcome such side effects, we have established a modular CAR platform termed UniCAR: UniCAR T cells per se are inert as they recognize a peptide epitope (UniCAR epitope) that is not accessible on the surface of living cells. Bifunctional adapter molecules termed target modules (TM) can cross-link UniCAR T cells with target cells. In the absence of TMs, UniCAR T cells automatically turn off. Until now, all UniCAR TMs were constructed by fusion of the UniCAR epitope to an antibody domain. To open up the wide field of low-molecular-weight compounds for retargeting of UniCAR T cells to tumor cells, and to follow in parallel the progress of UniCAR T cell therapy by PET imaging we challenged the idea to convert a PET tracer into a UniCAR-TM. For proof of concept, we selected the clinically used PET tracer PSMA-11, which binds to the prostate-specific membrane antigen overexpressed in prostate carcinoma. Here we show that fusion of the UniCAR epitope to PSMA-11 results in a low-molecular-weight theranostic compound that can be used for both retargeting of UniCAR T cells to tumor cells, and for non-invasive PET imaging and thus represents a member of a novel class of theranostics.